Comparison of Osteogenic Differentiation Potential of Human Dental-Derived Stem Cells Isolated from Dental Pulp, Periodontal Ligament, Dental Follicle, and Alveolar Bone - Guanlin Qu; Yan Li; Lu Chen; Qin Chen; Duohong Zou; Chi Yang; Qing Zhou (Hindawi Limited, 2021)
Background. Mesenchymal stem cells (MSCs) have become promising candidates for regeneration medicine due to their multidifferentiation potential and immunomodulatory ability. Compared with classic MSCs derived from the bone marrow and fat, dental-derived MSCs show high plasticity, accessibility, and applicability. Therefore, they are considered alternative sources for regeneration medicine. Methods. Four types of MSCs were isolated from the dental pulp, periodontal ligament, dental follicle, and alveolar bone of the same donor, and there were five different individuals. We analyzed their morphology, immunophenotype, proliferation rate, apoptosis, trilineage differentiation potential, and the gene expression during osteogenic differentiation. Results. Our research demonstrated that DPSCs, PDLSCs, DFPCs and ABMMSCs exhibited similar morphology and immunophenotype. DFPCs showed a higher rate of proliferation and apoptosis. When cultured in the trilineage differentiation medium, all types of MSCs presented the differentiation potential of osteogenesis, adipogenesis, and chondrogenesis. Through staining and genetic analysis during osteogenic induction, ABMMSCs and PDLSCs showed the highest osteogenic ability, followed by DPSCs, and DFPCs were the lowest. Conclusions. Overall, our results indicated that different dental-derived stem cells possessed different biological characteristics. For bone tissue engineering, ABMMSCs and PDLSCs can be used as optimal candidates of seed cells.